2019
DOI: 10.1111/jcmm.14866
|View full text |Cite
|
Sign up to set email alerts
|

A new trick for an old dog: The application of mifepristone in the treatment of adenomyosis

Abstract: Adenomyosis is also called internal endometriosis and affects about 20% of reproductive‐aged women. It seriously reduces life quality of patients because current drug therapies face with numerous challenges. Long‐term clinical application of mifepristone exhibits wonderful therapeutic effects with mild side‐effects in many disorders since 1982. Since adenomyosis is a refractory disease, we investigate whether mifepristone can be applied in the treatment of adenomyosis. In this study, we investigated the direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…The medium was then discarded, and the cells were gently washed with PBS to remove blood cells and debris. The purity of EuESCs in our experiment was >95%, as determined by positive immunostaining for vimentin and negative staining for cytokeratins-19 (Choi et al 2015, Che et al 2020. Second and third passages of cells were used for subsequent experiments.…”
Section: Isolation and Identification Of Endometrial Stromal Cellsmentioning
confidence: 95%
See 2 more Smart Citations
“…The medium was then discarded, and the cells were gently washed with PBS to remove blood cells and debris. The purity of EuESCs in our experiment was >95%, as determined by positive immunostaining for vimentin and negative staining for cytokeratins-19 (Choi et al 2015, Che et al 2020. Second and third passages of cells were used for subsequent experiments.…”
Section: Isolation and Identification Of Endometrial Stromal Cellsmentioning
confidence: 95%
“…However, they also share many similarities, including estrogen dependency, progesterone resistance, and multiple cellular and molecular aberrations (Vannuccini et al 2017, Kobayashi et al 2020, Zhu et al 2016. For many years, adenomyosis was considered a specific form of endometriosis called endometriosis interna (Vannuccini et al 2017, Che et al 2020. Although endometriosis and adenomyosis cause severe symptoms in patients, they are generally believed to be chronic benign uterine diseases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It restricts the migration of endometrial and stromal cells in adenomyosis. Therefore mifepristone can effectively inhibit the emergence and development of adenomyosis, decrease the uterine volume and cancer antigen-125 (CA-125) concentration, and increases the hemoglobin concentration in serum for adenomyosis patients [58,59]. In an interventional study of 20 adenomyosis patients on mifepristone 5 mg/day, there was significant relief concerning dysmenorrhea.…”
Section: Adenomyosismentioning
confidence: 99%
“…The authors found that mifepristone inhibited the cells' migratory capacity, inhibited their epithelial-mesenchymal transition, and induced apoptosis. From a clinical perspective, patients treated with mifepristone had a statistically significant decrease in uterine volume and statistically significant increase in hemoglobin in the 3 months on treatment prior to hysterectomy 80 …”
Section: Gynecologic Uses Of Mifepristonementioning
confidence: 99%